Impact of inter- and intra-observer variabilities of catheter reconstruction on multi-catheter interstitial brachytherapy of breast cancer patients. (June 2019) - Kallis, Karoline; Kaltsas, Theodoros; Kreppner, Stephan; Lotter, Michael; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph
Abstract: Purpose: The aim of this study was to evaluate inter- and intra-observer variabilities of catheter reconstruction and its dosimetric impact for multi-catheter interstitial breast cancer patients. Methods and materials: In order to evaluate inter-observer variabilities (IOV) three medical physicists reconstructed the catheter traces of 13 patients. These manual reconstructions were further compared to the automatic reconstruction algorithm integrated into the planning system and one on purpose imprecise manual reconstruction. For intra-observer variabilities (IAV) repeated reconstructions of two physicists were compared for 13 patients. In total 426 catheters were considered. Keeping dwell times, dwell positions, the optimization and the normalization relative points constant the geometrical deviations between the corresponding dwell positions of the reference data set and the investigated reconstructions were evaluated. Also, the effect on the quality indices, such as coverage index (CI), dose non-uniformity ratio (DNR) or conformal index (COIN), and the exposure of the organs at risk were analyzed. Results: Over all patients and all different catheter reconstructions considered for IOV a mean deviation between the corresponding dwell positions of 0.60 ± 0.35 mm was detected. The first observer had a mean deviation of 0.54 ± 0.32 mm, whereas the second observer yielded a mean deviation of 0.58 ± 0.37 mm. The length of the catheter traces varied in the mean by 0.51 ± 0.45 mm. The mean relative deviation of the CI, DNR, COIN, mean heart dose and mean lung dose varied by 0.27 ± 0.31%, 0.0027 ± 0.0025, 0.0036 ± 0.0033, 0.024 ± 0.019%, 0.05 ± 0.11%, respectively. The skin dose (D0.2ccm ) changed in the maximum 8.52%. On average IAV reached a deviation between the corresponding dwell positions of 0.49 ± 0.30 mm. IOVs and IAVs proved to be significantly different (Wilcoxon's test p < 0.01). Conclusions: The study proved that a repeated reconstruction of the catheter traces does not lead to large geometrical deviations or to a significant change in the dose exposure. But the lack of ground truth makes the estimation of the quality of the reconstruction challenging. A precise reconstruction mapping the reality is a necessity for the planned dose delivery. With all considered reconstruction techniques reliable quality indices for the target and the organs at risk could be obtained.